Use of bovine serum albumin might impair immunofluorescence signal in thick tissue samples - Anna Chwastowicz; Artur Wolny; Magdalena Sobień; Marcin Barański; Jacek Tomczuk; Michał Szatkowski; Aleksandra Szredzka; Jakub Gołąb; Leszek Kaczmarek; Marzena Stefaniuk; Paweł Matryba (Scientific Reports)
Abstract Significant progress in microscopic imaging techniques allowed transition from predominantly qualitative methods to a powerful tool for quantitative research, driven by improved instrumentation and computational power. Furthermore, previously limited to thin, laser-permeable tissue sections, imaging techniques have been revolutionized by the advent of tissue optical clearing. This innovation enables the visualization and quantitative analysis of entire organs and even whole bodies at cellular resolution. However, achieving high-quality imaging depends not only on the transparency of the tissue preparation but also on precise immunofluorescence labeling to ensure accurate signal detection and reliable study outcomes. In this study, we evaluated whether various reagents that are typically applied during the tissue blocking step prior to immunofluorescence staining affect the quality of the obtained image in thick and optically cleared samples. We demonstrate that the commonly employed tissue blocking step does not improve imaging conditions and even can substantially degrade fluorescence signal quality, particularly in large, optically cleared tissues such as whole mouse brain hemispheres.